2000
DOI: 10.5694/j.1326-5377.2000.tb139200.x
|View full text |Cite
|
Sign up to set email alerts
|

Trends in hospital readmission for asthma: has the Australian National Asthma Campaign had an effect?

Abstract: Objectives To describe patterns of hospital readmission for asthma in South Australia from 1989 to 1996, in relation to implementation of the National Asthma Campaign. Design and setting A comparison of hospital admissions in South Australia of patients aged between one year and 49 years for three conditions: asthma (or respiratory failure with asthma as an underlying condition) and two control conditions — diabetes and epilepsy. Individuals were identified by Medicare number and date of birth. Outcome measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…Other investigators have assessed the rate of readmission after discharge from a previous asthma-related hospitalization, and factors altering such rates [6,18-21]. But these studies have not attempted to contrast the risk in the post-discharge period with control periods, and thus have not been able to show any change in the risk.…”
Section: Discussionmentioning
confidence: 99%
“…Other investigators have assessed the rate of readmission after discharge from a previous asthma-related hospitalization, and factors altering such rates [6,18-21]. But these studies have not attempted to contrast the risk in the post-discharge period with control periods, and thus have not been able to show any change in the risk.…”
Section: Discussionmentioning
confidence: 99%
“…General practitioners have been effective in other health promotion areas, such as smoking, 9 alcohol, 10 adolescent health care 11 . The National Asthma Campaign was successful in both educating GPs and enhancing the asthma management by both GPs and parents, resulting in reduced hospital admission rates and asthma mortality 12,13 . Controlled primary care trials have shown some effectiveness targeting adult overweight, healthy eating and physical activity 14 .…”
mentioning
confidence: 99%
“…11 The National Asthma Campaign was successful in both educating GPs and enhancing the asthma management by both GPs and parents, resulting in reduced hospital admission rates and asthma mortality. 12,13 Controlled primary care trials have shown some effectiveness targeting adult overweight, healthy eating and physical activity. 14 However, no reported trials have yet examined the efficacy of GPs in managing childhood overweight and mild obesity, and the feasibility of this approach is unknown.…”
mentioning
confidence: 99%
“…In Finland, the median duration of admission was 2.0 days in children (15). In South Australia, it was around 2.8 days for patients 1–49 yr with asthma from 1989 to 1996 (16). In our data, it was 4.4 days in the children group and 2.6 times higher in the adult group.…”
Section: Discussionmentioning
confidence: 99%
“…The readmission rate declined in Oslo, Norway during the period of 1980 to 1995 as well (18). In Australia, there was also a significant decline in readmission of 17% in the 1990s (16). On the contrary, in Athens, the readmission rate among children 0–14 yr increased from 15.3% to 23.3%, and there were no significant differences between the younger and older groups (5).…”
Section: Discussionmentioning
confidence: 99%